The Role of Gender, Sexual Assault History, and Sexism in Endorsement of Rape Myths Among College Students - Wilson, Laura C. (Violence against women, 2024)
The present study examined the roles of sexual victimization history, sexism toward women, and sexism toward men in the gender difference in rape myth acceptance. The data were obtained from 2,011 male and female college students who completed an online survey. The results suggested that gender had a significant indirect effect on rape myth acceptance via sexual assault history and several forms of sexist beliefs. The findings supported the importance of considering additional antecedents of rape myths in research, as well as in programming geared toward preventing sexual assault and improving support for survivors.